1985
DOI: 10.1073/pnas.82.10.3481
|View full text |Cite
|
Sign up to set email alerts
|

Immunological properties of the Gag protein p24 of the acquired immunodeficiency syndrome retrovirus (human T-cell leukemia virus type III).

Abstract: Antigenic cross-reactivity of human T-cell leukemia virus type III (HTLV-III) with HTLV-I and HTLV-II and other retroviruses was measured by using a stringent homologous competition radioimmunoassay for the Gag protein p24 and a less stringent electrophoretic transfer blot assay. In the competition radioimmunoassay only minimal crossreactivities were detected between HTLV-III p24 and both HTLV-I and HTLV-II. No cross-reactivity was detected with any other retrovirus. In the electrophoretic transfer blot system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 20 publications
(26 reference statements)
1
26
0
Order By: Relevance
“…The minimum criteria used to identify new HTLV-III isolates were (i) release of particulate, Mg2+-requiring, viral reverse transcriptase into cell culture supernatant fluids (1, 2); (ii) transmission of virus to cultures of normal human peripheral blood mononuclear cells or to permissive T-cell lines with resulting characteristic cytopathic effects and release of virus (1, 2); and (iii) detection of HTLV-III proteins by indirect immunofluorescence assays using virus-specific monoclonal antibody (13) or hyperimmune sera (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The minimum criteria used to identify new HTLV-III isolates were (i) release of particulate, Mg2+-requiring, viral reverse transcriptase into cell culture supernatant fluids (1, 2); (ii) transmission of virus to cultures of normal human peripheral blood mononuclear cells or to permissive T-cell lines with resulting characteristic cytopathic effects and release of virus (1, 2); and (iii) detection of HTLV-III proteins by indirect immunofluorescence assays using virus-specific monoclonal antibody (13) or hyperimmune sera (12).…”
Section: Resultsmentioning
confidence: 99%
“…Six individual virus isolates further characterized by detailed immunological and nucleic acid analyses also showed relatedness to each other. Details of the protein and nucleic acid comparisons of virus isolates of HTLV-Ill have been presented elsewhere (3,4,10,12,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, infections with HIV-I result in the for- Reactivity with monoclonal antibodies against HIV-I p17 and p24 (IGSS technique) reported semiquantitatively as percentage of cells labeled ( -0%, + 0.1-1 %, + + 2-5%, + + + 5%, ND: not done) mation of antibodies to virion structural as well as envelope glycoprotein antigens (32,33). We, as well as other investigators (15) were not able to detect antibodies to HIV-I viral antigens in sera of RA patients by ELISA and immunoblotting.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that the pattern of serological reactivity observed with lentiviruses is dependent on the immunoassay employed (Montagnier et al, 1984;Sarngadharan et al, 1985;Goudsmit et al, 1986). Thus, we performed a series of immunoassays (RIP, RIA and immunoblot) to ascertain the reactivity of the respective purified surface glycoproteins of HIV (gpl20) (Robey et al, 1986) and EIAV (gp90) (Parekh et al, 1980) against a panel of sera including an AIDS patient serum pool (Robey et al, 1986), a goat serum raised against purified HIV gpl20 (Robey et al, 1986), and reference sera from horses naturally infected with EIAV (Montelaro et al, 1984a, b).…”
mentioning
confidence: 99%